2021
DOI: 10.1270/jsbbs.19106
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry fruit shape: quantification by image analysis and QTL detection by genome-wide association analysis

Abstract: Fruit shape of cultivated strawberry ( Fragaria × ananassa Duch.) is an important breeding target. To detect genomic regions associated with this trait, its quantitative evaluation is needed. Previously we created a multi-parent advanced-generation inter-cross (MAGIC) strawberry population derived from six founder parents. In this study, we used this population to quantify fruit shape. Elliptic Fourier descriptors (EFDs) were generated from 2 969 two-dimensional bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…GWAS is a powerful tool for the detection of SNP markers linked to different traits in strawberry 9,17,28,30,36,37 . Here, based on a large diversity panel, we detected 71 markers associations to major fruit quality breeding targets.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS is a powerful tool for the detection of SNP markers linked to different traits in strawberry 9,17,28,30,36,37 . Here, based on a large diversity panel, we detected 71 markers associations to major fruit quality breeding targets.…”
Section: Discussionmentioning
confidence: 99%
“…Although visual evaluation is a widely used nondestructive method for grading and sorting in horticultural crops, utilization of high-throughput phenotyping platforms is essential to obtain robust, faster, and objective results [ 14 ]. Nowadays, quantitative measurement of these traits (color, size, shape, and surface texture) using image analysis is increasingly used in different horticultural crops [ 13 , 84 , 85 , 86 , 87 ].…”
Section: Applications Of Image-based High-throughput Phenotyping In H...mentioning
confidence: 99%
“…RGB and HSI are able to separate within the noir and non-noir groups and enable the identification of minor QTLs controlling grape berry color, which were not identified previously using qualitative evaluation [ 89 ]. Quantitative measurement of strawberry fruit shape based on elliptic Fourier descriptors (EFDs) [ 90 ] and image analysis allowed the identification of two QTLs for shape via a genome-wide association study [ 84 ]. The fruit shape was highly correlated with the fruit length-to-width ratio.…”
Section: Applications Of Image-based High-throughput Phenotyping In H...mentioning
confidence: 99%
“…However, the researchers reported that two QTLs were mapped in LGIII and LGIV for the neck without achenes regions. On the other hand, Nagamatsu et al [56] conducted a study in order to identify QTLs associated with fruit shape using a MAGIC population derived from full-sib families. In genome-wide association analysis, QTL regions were detected within chromosomes 6 and 7 in genome-wide association analysis.…”
Section: Qtls Related To the Morphological And Biochemical Traits In ...mentioning
confidence: 99%